Feedforward and feedback projections of caudal belt and parabelt areas of auditory cortex: refining the hierarchical model - Hackett, Troy A.; de la Mothe, Lisa A.; Camalier, Corrie R.; Falchier, Arnaud; Lakatos, Peter; Kajikawa, Yoshinao; Schroeder, Charles E. (Frontiers in Neuroscience, 2014)
Our working model of the primate auditory cortex recognizes three major regions (core, belt, parabelt), subdivided into thirteen areas. The connections between areas are topographically ordered in a manner consistent with information flow along two major anatomical axes: core-belt-parabelt and caudal-rostral. Remarkably, most of the connections supporting this model were revealed using retrograde tracing techniques. Little is known about laminar circuitry, as anterograde tracing of axon terminations has rarely been used. The purpose of the present study was to examine the laminar projections of three areas of auditory cortex, pursuant to analysis of all areas. The selected areas were: middle lateral belt (ML); caudomedial belt (CM); and caudal parabelt (CPB). Injections of anterograde tracers yielded data consistent with major features of our model, and also new findings that compel modifications. Results supporting the model were: 1) feedforward projection from ML and CM terminated in CPB; 2) feedforward projections from ML and CPB terminated in rostral areas of the belt and parabelt; and 3) feedback projections typified inputs to the core region from belt and parabelt. At odds with the model was the convergence of feedforward inputs into rostral medial belt from ML and CPB. This was unexpected since CPB is at a higher stage of the processing hierarchy, with mainly feedback projections to all other belt areas. Lastly, extending the model, feedforward projections from CM, ML, and CPB overlapped in the temporal parietal occipital area (TPO) in the superior temporal sulcus, indicating significant auditory influence on sensory processing in this region. The combined results refine our working model and highlight the need to complete studies of the laminar inputs to all areas of auditory cortex. Their documentation is essential for developing informed hypotheses about the neurophysiological influences of inputs to each layer and area.